2012
DOI: 10.1261/rna.033977.112
|View full text |Cite
|
Sign up to set email alerts
|

Coat color determination by miR-137 mediated down-regulation of microphthalmia-associated transcription factor in a mouse model

Abstract: Coat color is a key economic trait in wool-producing species. Color development and pigmentation are controlled by complex mechanisms in animals. Here, we report the first production of an altered coat color by overexpression of miR-137 in transgenic mice. Transgenic mice overexpressing miR-137 developed a range of coat color changes from dark black to light color. Molecular analyses of the transgenic mice showed decreased expression of the major target gene termed MITF and its downstream genes, including TYR,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
77
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(81 citation statements)
references
References 33 publications
3
77
1
Order By: Relevance
“…Our results show that UV treatment in fish leads to the activation of a-MSH and the MC1R gene. The result is similar to that previously reported in keratinocytes (Dong et al, 2012). By contrast, miR-429 knockdown has no effect on the level of a-MSH and MC1R expression with or without UV radiation.…”
Section: Altered Expression Of Pigmentation Genes In Mir-429 Silencinsupporting
confidence: 91%
See 3 more Smart Citations
“…Our results show that UV treatment in fish leads to the activation of a-MSH and the MC1R gene. The result is similar to that previously reported in keratinocytes (Dong et al, 2012). By contrast, miR-429 knockdown has no effect on the level of a-MSH and MC1R expression with or without UV radiation.…”
Section: Altered Expression Of Pigmentation Genes In Mir-429 Silencinsupporting
confidence: 91%
“…Skin pigmentation in fish is a complex process that involves a series of cellular, genetic and physiological factors (Colihueque, 2010). The role of miRNAs in pigmentation has been reported in some species, including mouse, alpaca and Drosophila (Dong et al, 2012;Kennell et al, 2012;Zhu et al, 2010). In this study, we revealed that miR-429 is a potential regulator of fish pigmentation.…”
Section: Altered Expression Of Pigmentation Genes In Mir-429 Silencinmentioning
confidence: 62%
See 2 more Smart Citations
“…In recent years, the regulatory mechanisms of alpaca fiber growth and coat color have aroused scientific interest, due to the excellent quality of alpaca wool Fan et al, 2010;Zhu et al, 2010;Dong et al, 2012). It has been recently shown that microRNAs (miRNAs) play pivotal roles in skin morphogenesis and development, and are involved in a variety of skin diseases, including cancer (Sand et al, 2009).…”
Section: Introductionmentioning
confidence: 99%